The Mycophenolate-based Immunosuppressive Regimen Is Associated with Increased Mortality in Kidney Transplant Patients with COVID-19 - Requião-Moura, Lúcio R. (2022)
Background. The chronic use of immunosuppressive drugs is a key risk factor of death because of coronavirus disease 2019 (COVID-19) in kidney transplant recipients (KTRs), although no evident association between the class of immunosuppressive and outcomes has been observed. Thus, we aimed to compare COVID-19-associated outcomes among KTRs receiving 3 different immunosuppressive maintenance regimes. Methods. This study included data from 1833 KTRs with COVID-19 diagnosed between March 20 and April 21 extracted from the national registry before immunization. All patients were taking calcineurin inhibitor associated with mycophenolate acid (MPA, n = 1258), azathioprine (AZA, n = 389), or mammalian targets of rapamycin inhibitors (mTORi, n = 186). Outcomes within 30 and 90 d were assessed. Results. Compared with patients receiving MPA, the 30-d (79.9% versus 87.9% versus 89.2%; P < 0.0001) and 90-d (75% versus 83.5% versus 88.2%; P < 0.0001) unadjusted patient survivals were higher in those receiving AZA or mTORi, respectively. Using adjusted multivariable Cox regression, compared with patients receiving AZA, the use of MPA was associated with a higher risk of death within 30 d (adjusted hazard ratio [aHR], 1.70; 95% confidence interval [CI], 1.21-2.40; P = 0.003), which was not observed in patients using mTORi (aHR, 0.78; 95% CI, 0.45-1.35; P = 0.365). At 90 d, although higher risk of death was confirmed in patients receiving MPA (aHR, 1.46; 95% CI, 1.09-1.98; P = 0.013), a reduced risk was observed in patients receiving mTORi (aHR, 0.59; 95% CI, 0.35-0.97; P = 0.04) compared with AZA. Conclusions. This national cohort data suggest that, in KTRs receiving calcineurin inhibitor and diagnosed with COVID-19, the use of MPA was associated with higher risk of death, whereas mTORi use was associated with lower risk of death.